A call for the standardised reporting of factors affecting the exogenous loading of extracellular vesicles with therapeutic cargos - O'Driscoll, Lorraine (My University, 2021)
Extracellular vesicles (EVs) are complex nanoparticles required for the intercellular transfer of diverse biological cargoes. Unlike synthetic nanoparticles, EVs may provide a natural platform for the enhanced targeting and functional transfer of therapeutics across complex and often impenetrable biological boundaries (e.g. the blood–brain barrier or the matrix of densely organised tumours). Consequently, there is considerable interest in utilising EVs as advanced drug delivery systems for the treatment of a range of challenging pathologies. Within the past decade, efforts have focused on providing standard minimal requirements for conducting basic EV research. However, no standard reporting framework has been established governing the therapeutic loading of EVs for drug delivery applications. The purpose of this review is to critically evaluate progress in the field, providing an initial set of guidelines that can be applied as a benchmark to enhance reproducibility and increase the likelihood of translational outcomes.
Keywords: drug delivery applications; Extracellular vesicles (EVs); nanoparticles; drug delivery applications; Extracellular vesicles (EVs); nanoparticles